THE PERCEPTION OF ELDERLY PRACTITIONERS OF PHYSICAL ACTIVITIES ON HEALTHY EATING: A CASE STUDY (Fiep Bulletin - online, 2013)
Aging is a phenomenon that brings changes over the years and despite being a natural process, the body undergoes several anatomical and functional, with impacts on health and nutrition. One should therefore assess the living conditions of the elderly, for implementation of alternative intervention in order to improve the quality of life and physical and mental wellbeing. The aim of this study was to identify the elderly with physical activities practitioners of a Social Action Program, their perceptions about healthy eating, with a view to enhance the autonomy of elderly food involved. Characterized as a case study, qualitative, cross-sectional, exploratory research was conducted in São Leopoldo - RS, Brazil, with 19 subjects, all older than 60 years, engaged in physical activity. Information was collected individual's dietary history (interviews) and were anthropometric measurements (weight, height, BMI). The study concludes that respondents have clear understanding about healthy eating, describing it as a well-balanced diet, healthier, reducing salt, fat and sugar, more vegetables, and natural products, with the inclusion of grains. Although the design suitable for the elderly on the subject, they associate it only to food, not knowing properly need the necessary amounts of intake for this phase of life, which is confirmed with anthropometric, where 68.42% of the participants overweight. The study reinforces the importance of extreme Nutritionist in implementing projects that include physical activity in the elderly, in order to maintain health, prevent disease and improve quality of life.
Keywords: Aging; Eating; Physical activity.